Linguistic realization of marketing strategies in food discourse: a pragmatic study on Instagram account - Sudartinah, Titik; Nursanti, Emi; Arrum, Regita Sekar (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
In today's digital era, speech acts are not only realized through face-to-face communication but also manifested in online interaction. One of the prominent platforms where online interaction occurs is Instagram. Nowadays, Instagram functions not only as a medium for sharing personal moments but also as a powerful business tool for promotion. This study examines (1) the types of speech acts employed in the @voilajogja culinary Instagram account and (2) how these acts manifest marketing strategies in food discourse. The study applies Searle's (1979) speech act theory and Kotler and Keller's (2021) marketing management framework within a mixed-method design. The analysis focuses on captions posted during the Ramadan period (March 1–31, 2025). The findings reveal that representative speech acts are the most salient (94.3%), functioning to inform users about restaurant locations, operating hours, and recommended menu items. Commissive acts (42.9%) appear in the form of promotional promises such as buy 5 get 1 free, 50% discounts for children under 12 years old. Directive acts (25.7%) encourage followers to make reservations or order specific dishes. Expressive acts (28.6%) convey positive evaluations and admiration for the food and ambiance. Notably, declarative acts are absent aligning with Instagram's informal and promotional nature. Drawing on Kotler and Keller's (2021) marketing communication framework, these linguistic patterns represent the integration of informative, persuasive, and emotional strategies to attract and engage consumers. Overall, the findings suggest that food promotion on Instagram functions not only as a digital marketing practice but also as a site of pragmatic interaction where marketing strategies are linguistically realized.